Abnormally Altered Patterns of Whole Brain Functional Connectivity Network of Posterior Cingulate Cortex in Remitted Geriatric Depression: A Longitudinal Study. (17th March 2014) - Jiang, Wen‐Hao; Yuan, Yong‐Gui; Zhou, Hong; Bai, Feng; You, Jia‐Yong; Zhang, Zhi‐Jun
Summary Aims A longitudinal study investigated the remitted geriatric depression (RGD) patients' persistent cognitive impairment and potential correlation with their PCC functional connectivity network. Methods A total of 14 RGD patients and 18 matched controls were recruited. All subjects finished the neuropsychological tests and functional magnetic resonance imaging scan at baseline and follow‐up. A spherical region of interest was placed in PCC to calculate the functional connectivity, and further analysis was employed to detect correlations between longitudinal changes in the brain regions and neuropsychological data. Results There were significant cognitive declines in RGD patients at baseline and follow‐up. Altered patterns of functional connectivity were detected within the RGD group showing correlations with neuropsychological tests. The longitudinal change in functional connectivity between PCC and cerebellum posterior lobe was correlated with longitudinal changes in auditory verbal memory test‐recall (r = 0.550, P = 0.042). The longitudinal change in functional connectivity between PCC and right parahippocampal gyrus was correlated with Trail Making Test‐A (r = 0.631, P = 0.015). The longitudinal change in functional connectivity between PCC and supramarginal_R was correlated with Mini‐Mental State Examination (r = −0.630, P = 0.016). Conclusions RGD patients performed worse cognitive function, and altered PCC functional connectivity network might have a role in these cognitive declines.